DAMPAK PENINGKATAN TARIF IMPOR GULA TERHADAP PENDAPATAN PETANI TEBU - MALIAN, A. HUSNI; -, SAPTANA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 2 Juli 2003)
International sugar price tended to decline during 2002 due to high stock sugar in producing countries and high import tariff by consumed countries. Such condition resulting negative impact for sugar cane farmers. Therefore, government increased import tariff to 700/kg to increase farmer’s income. Based on some assumptions; price of white sugar cane in the world US $ 225/ton, value of exchange rate Rp. 8,500 – Rp. 8,700/US $, a range of rendemen 6.00 – 6.50 % and farmers receive management fee 20 % from BEP; specific tariff range from Rp 950,- to Rp 1,300/kg. To reduce the negative impact, government provided subsidized to farmers calculated from BEP + 20% (management fee) subtracted by lelang price at farmer level.
Keywords: International Sugar Price, Sugar Cane Farmer, Import Tariff, Negative Impact, and Subsidized